BACTERIAL RESISTANCE FROM FORMER MINING EXCAVATIONS IN LOA BAHU VILLAGE TO HEAVY METALS Pb, Cd, AND Cr - Trista Kinanthi Putri Santoso; Winni Astuti; Djihan Ryn Pratiwi (Jurusan Kimia FMIPA UNMUL, 2026)
Ex-mining lakes are one of the potential sources of bacteria that are resistant to metals. The purpose of this study was to isolate bacteria from the lake in Loa Bahu village as metal bioremediation agents. The research was conducted by taking lake water samples at three different points in Loa Bahu village, Sungai Kunjang, Samarinda. Bacteria were isolated in agar solid media (NA) by streak method using an ose needle and 13 bacterial isolates were taken. Bacteria were selected with heavy metals Pb 100 ppm, Cd 30 ppm, and Cr 30 ppm using agar solid media (NA). The selection results are all bacterial isolates resistant to metal Pb 100 ppm, 6 bacterial isolates resistant to metal Cd 30 ppm, 4 bacterial isolates resistant to metal Cr 30 ppm. The best potential is found in AT 3 bacteria because it is able to grow in all types of metals.